2016
DOI: 10.3389/fmicb.2016.00233
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Gene Repertoire of Gigaspora rosea Unravels Conserved Features among Glomeromycota for Obligate Biotrophy

Abstract: Arbuscular mycorrhizal (AM) fungi are a diverse group of soil fungi (Glomeromycota) that form the most ancient mutualistic association termed AM symbiosis with a majority of land plants, improving their nutrition uptake and resistance to stresses. In contrast to their great ecological implications, the knowledge of the molecular biological mechanisms involved is still scant, partly due to the limited genomic resources available. Here, we describe the gene repertoire of a new AM fungus Gigaspora rosea (Diversis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
122
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 141 publications
9
122
0
2
Order By: Relevance
“…AMF are lipid auxotrophs, and accordingly, lipids are transferred from the host plant to AMF to sustain AM colonization [126][127][128], which requires action of the glycerol-3-phosphate acyltransferase enzyme Required for Arbuscular Mycorrhization 2 (RAM2) [129]. Jiang et al (2017) showed that plant fatty acids are also transferred to the powdery mildew pathogen, Golovinomyces cichoracerum (DC.)…”
Section: Potential Trade-offsmentioning
confidence: 99%
“…AMF are lipid auxotrophs, and accordingly, lipids are transferred from the host plant to AMF to sustain AM colonization [126][127][128], which requires action of the glycerol-3-phosphate acyltransferase enzyme Required for Arbuscular Mycorrhization 2 (RAM2) [129]. Jiang et al (2017) showed that plant fatty acids are also transferred to the powdery mildew pathogen, Golovinomyces cichoracerum (DC.)…”
Section: Potential Trade-offsmentioning
confidence: 99%
“…In addition, the RNA-seq data analysis coupled with gene expression profiling show that both G. margarita and Gigaspora rosea consist of multiple distinct SPX domaincontaining proteins ( Salvioli et al, 2016 andTang et al, 2016), indicative of the existence of potential Pi sensors in AM fungi to respond to cellular Pi levels through binding inositol polyphosphate in eukaryotes (Wild et al, 2016) and adapting to fluctuation of available phosphate. Thus, a major goal in this field will be to unravel a potential master cellular Pi sensor controlling AM fungal Pi homeostasis during symbiosis.…”
Section: Conservation Of Pho and Pka Pathways In Am Fungi And Dual Romentioning
confidence: 99%
“…It is noteworthy that Medtr4g097510 is one of the 12 lipid biosynthetic genes only expressed in AM symbiotic hosts (Bravo et al 2016). This suggests that, similarly to the thioesterase FatM, the ketoacyl-acyl carrier reductase KAR, and the ketoacyl-ACP synthase KAS II (Bravo et al 2017;Jiang et al 2017), the PMassociated enoyl-(acyl carrier) reductase may contribute to supply FAs to the AM symbiont which cannot synthetize C16:0 FAs Tang et al 2016). In support of this idea, the beta-hydroxyacyl-(acyl-carrier-protein) dehydratase FabZ (Medtr4g094265) that leads to the synthesis of palmitate (C16:0) was only detected in the PM fraction of AM roots (Table S1).…”
Section: Am-responsive Proteins As Related To Interface Biogenesis Anmentioning
confidence: 99%